Validation of new indices for differentiation between iron deficiency anemia and beta thalessemia trait, a study in pregnant females - Arora, Sheetal; Rana, Deepshikha; Kolte, Sachin; Dawson, Leelawathi; Dhawan, Indrani (International Journal of Scientific Reports, 2018)
Background: The two most frequent types of microcytic hypochromic anemia in developing countries are beta thalassemia trait (????-TT) and iron deficiency anemia (IDA). Several indices using blood cell count parameters have been suggested to differentiate between two. In this study we evaluated the reliability of three indices. Methods: The present cross-sectional study was carried out in 300 pregnant females in third trimester. Out of these, 90 microcytic hypochromic females were selected. Mentzers index, red cell distribution width index and Matos and Carvalho index (MCI) were calculated from the regular 3-part analyser haematological parameters. Results: The Mentzer index was the most reliable index, as it had the highest sensitivity (97.62%), specificity (66.67%), and Youden’s index (64%) for detecting Iron deficiency anaemia; the Matos and Carvalho Index showed higher sensitivity (98.81%)but a much lower specificity (33.3%) and Youden’s index (32%) while the red cell distribution width index showed the sensitivity and specificity of 92.86% and 66.67%, respectively with Youden’s index of 59%. Conclusions: The Mentzer index provided the highest reliabilities for differentiating IDA from ????-TT. The new indices have high sensitivities and positive predictive value for identifying IDA, making them useful for screening population at risk.